Integrated Reporting and Its Role in Reducing the Asymmetry of Accounting Information for Investors - Muna Hameed Saadoon (Harmoni Economics: International Journal of Economics and Accounting, 2025)
Integrated reports represent a disclosure of the vision, mission and strategy of companies towards achieving their current and future goals". They link environmental, social, governance and economic performance, and act as a link and communication between stakeholders and companies to assess the ability of companies to create and maintain value. "In order to ascertain whether integrated reports contribute to lessening the asymmetry of accounting information among investors when they are making investment decisions, the current study intends to investigate the relationship between integrated reports and the phenomenon of asymmetry of accounting information among investors". The study concluded the importance of companies shifting to integrated reports, "which in turn leads to reducing the asymmetry of accounting information among investors, in addition to the urgent need to spread awareness of the positive aspects of integrated reports".